The signature of the small intestinal epithelial and immune cells in health and diseases - Xiang Gao; Cuiping Yang; Zhongsheng Feng; Ping Liu; Zhanju Liu; Yuanyuan Ji (Chinese Medical Journal)
Abstract. The small intestine is essential for digestion, nutrient absorption, immune regulation, and microbial balance. Its epithelial lining, containing specialized cells like Paneth cells and tuft cells, is crucial for maintaining intestinal homeostasis. Paneth cells produce antimicrobial peptides and growth factors that support microbial regulation and intestinal stem cells, while tuft cells act as chemosensors, detecting environmental changes and modulating immune responses. Along with immune cells such as intraepithelial lymphocytes, innate lymphoid cells, T cells, and macrophages, they form a strong defense system that protects the epithelial barrier. Disruptions in this balance contribute to chronic inflammation, microbial dysbiosis, and compromised barrier function—key features of inflammatory bowel disease, celiac disease, and metabolic syndromes. Furthermore, dysfunctions in the small intestine and immune cells are linked to systemic diseases like obesity, diabetes, and autoimmune disorders. Recent research highlights promising therapeutic strategies, including modulation of epithelial and immune cell functions, probiotics, and gene editing to restore gut health and address systemic effects. This review emphasizes the pivotal roles of small intestinal epithelia and immune cells in maintaining intestinal homeostasis, their involvement in disease development, and emerging treatments for intestinal and systemic disorders.